Analisis Faktor-Faktor Yang Mempengaruhi Kelancaran Pengembalian Kredit Pada Pt Bank Pembangunan Daerah Jawa Barat Dan Banten Tbk Cabang XYZ - Krisdiana Krisdiana (EBBANK, 2013)
This study entitled "The Analysis of Factors that Influence the performance of credit in bank bjb xyz". The purpose of this research is to know the effect of interest rate, term of loans, credit plafond , age, collateral type, installment, debitor economic sector and income to credit performance at bjb xyz branch. This study uses Binary Logistic Regression with sample 43 account of micro-credit debitors in bjb xyz branch, the sampling method that being used is random sampling. The results of this research showed only three variables that significantly influence credit performance there are interest rate, age and type of collateral. Meanwhile term of loans, credit plafond, installment, debitor economy sector, have no significant effect on credit performance.  Based on the results of this study, writer suggest that bjb xyz branch  focus on the lending rates factor to optimize bank bjb xyz earnings, but still be able to win with the compatitors. Debitors age also need to be considered because it relates to past experience and the top of debitors productivity. Regards on types of collateral, bank may consider to choose the collateral based on credit plafond given and credit risks taken, the higher credit plafond given, the bigger the credit risk exposure so it must be supported with an adequate collateral.